Studies of sulfated bile acids in sera of patients with hepatobiliary diseases - NISHIMURA, Daisaku; SATAKE, Tatsuo; KUMADA, Takashi; IMOTO, Masami; FUKUDA, Yoshihide; SUGIYAMA, Keiichi; OKUYAMA, Sumihiko (Kanzo, 1986)
In this study, we present a method of measurement of sulfated bile acids by enzymatic hydrolysis using sulfatase, and measure concentration of sulfated bile acids in serum samples of 10 normal subjects and 81 patients with hepatobiliary diseases. Serum levels of sulfated bile acids increased in patients with acute hepatitis, extrahepatic or intrahepatic cholestasis. And the percentage of sulfated bile acids to total bile acids in serum samples of patients with fulminant hepatitis or decompensated liver cirrhosis was significantly lower than that in serum samples of patients with acute hepatitis or compensated liver cirrhosis (p<0.01). There were also positive correlation between the percentage of sulfated bile acids in sera and thrombotest, normotest, prothrombin time and α2-heat-stable-glycoprotein (p<0.01 or p<0.05). From these results, it is considered that measurement of serum levels of sulfated bile acids can be efficient indicator in the diagnosis of the development of liver damage.